American odyssey : Haitians in New York City - Laguerre, Michel S. (Cornell University Press, 1984)
Caribbean immigrants have now become part of the social landscape of many American cities. Few studies, however, have treated in detail the process of their integration in American society. American Odyssey assesses the development and adaptation, in both human and socio-economic terms, of the Haitian immigrant community in three boroughs of New York City. An informed and well-rounded portrayal of a Caribbean community in New York, this book offers a fresh theoretical view of the structuring of urban ethnicity and provides the ethnographic background essential to understanding the problems of the Haitian population in the United States.